ICT, Financial Inclusion, and Growth : Evidence from African Countries - Kpodar, Kangni (IMF Working Papers; Working Paper ;, 2011)
This paper studies the impact of information and communication technologies (ICT), especially mobile phone rollout, on economic growth in a sample of African countries from 1988 to 2007. Further, we investigate whether financial inclusion is one of the channels through which mobile phone development influences economic growth. In estimating the impact of ICT on economic growth, we use a wide range of ICT indicators, including mobile and fixed telephone penetration rates and the cost of local calls. We address any endogeneity issues by using the System Generalized Method of Moment (GMM) estimator. Financial inclusion is captured by variables measuring access to financial services, such as the number of deposits or loans per head, compiled by Beck, Demirguc-Kunt, and Martinez Peria (2007) and the Consultative Group to Assist the Poor (CGAP, 2009). The results confirm that ICT, including mobile phone development, contribute significantly to economic growth in African countries. Part of the positive effect of mobile phone penetration on growth comes from greater financial inclusion. At the same time, the development of mobile phones consolidates the impact of financial inclusion on economic growth, especially in countries where mobile financial services take hold.